The Association of Intake of Omega-3-Fatty Acid Sources with Psychological Distress and Binge Eating Disorder Among Female College Students in Saudi Arabia - Rana Mosli; Hajer Alsulami; Raghad Alghamdi; Hebah Kutbi (Nutrition and Metabolic Insights)
University students are often exposed to various stressors related to academic demands, which increases their susceptibility to psychological distress. Intake of omega-3 fatty acid (N-3 FA) has been found to be negatively correlated with both depression and eating disorder symptoms in non-Saudi individuals. The objective of this study was to evaluate the following among female undergraduate students in Jeddah, Saudi Arabia: (1) prevalence of psychological distress and binge eating disorder (BED); (2) Association between intake of N-3 FA sources and psychological distress; (3) Association between intake of N-3 FA sources and BED. This is a cross-sectional study including 149 female students enrolled in King Abdulaziz University. Participants completed an online questionnaire consisting of previously validated questions that evaluate psychological distress (Kessler 10), BED (Eating Disorders Diagnostic Scale), and N-3 FA intake. Descriptive statistics and logistic regression analysis were performed to analyze the data. The prevalence of mild, moderate, and severe psychological distress was 21.5%, 28.9%, and 28.20%, respectively. The prevalence of BED was 3.40%. Participants who consumed fish at least once per week for 6 months had significantly lower odds of moderate or severe psychological distress (odds ratio (OR): 0.34, 95% confidence interval (CI): 0.13, 0.86, P -value: .02). We did not detect significant associations between intake of N-3 FA sources and BED. Prevalence of psychological distress was higher what has been previously reported in other studies. However, prevalence of BED in our Saudi sample was lower than what has been previously found in other samples. Intake of N-3 FA from fish sources might be associated with lower odds of psychological distress but not with BED. Future studies are needed in order to further establish the need for developing educational programs to enhance N-3 FA intake for promoting mental wellbeing particularly among female young adults.